Population Pharmacokinetics of Glasdegib in Patients With Advanced Hematologic Malignancies and Solid Tumors. (25th November 2019) - Lin, Swan; Shaik, Naveed; Martinelli, Giovanni; Wagner, Andrew J.; Cortes, Jorge; Ruiz‐Garcia, Ana
Abstract: Glasdegib is an inhibitor of the Hedgehog pathway recently approved in the United States for the treatment of acute myeloid leukemia. A population pharmacokinetic analysis was conducted to characterize the kinetic behavior of glasdegib and its sources of variability (covariates) by utilizing data from 269 patients with cancer treated with oral glasdegib doses ranging from 5 to 640 mg/d. Nonlinear mixed‐effects modeling was conducted using NONMEM (v.7.3) and Perl‐speaks NONMEM (v.4.2.0). The estimated apparent total clearance, apparent central volume of distribution, and apparent peripheral volume of distribution were 6.27 L/h, 3.32 L, and 279.2 L, respectively. Age, sex, race, and hepatic function were not significant covariates on glasdegib pharmacokinetic parameters. Baseline body weight, percentage bone marrow blasts, creatinine clearance, and use of moderate or strong cytochrome P450 3A inhibitors were statistically significant covariates on apparent total clearance; however, the magnitude of the effects was not considered clinically meaningful.